Who Are You Re? The Pragmatic Implication of Fela Kuti’s Question - Bamigboye, Omolade (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The paper adopts a pragmatic approach to the understanding of a question posed by the late Fela Anilulapo-Kuti in one of his evergreen musical compositions. The underlying meaning of a borrowed word in the expression is systematically investigated with a view to determining its actual purpose and comprehension with respect to the peculiar Nigerian linguistic environment. The finding is that the word conveys an underlying meaning sensitive only to its contextual occurrence. The paper concludes that more attention be paid to the infusion of foreign words in the contextual use of language.